Thursday

March 26, 2015

March 26, 2015

Posted by **Marissa** on Monday, September 8, 2008 at 3:55am.

∫ x^3√(9-x^2) dx

So then I know that

x = 3sinθ

dx = 3cosθdθ

When I substitute, it becomes

∫ (3sinθ)^3 * √(9-(3sinθ)^2) * 3cosθdθ

= ∫ (27sin^3θ * (3 - 3sinθ)* 3cosθdθ

Is there any way to furter simplify this before I solve it? And if there isn't, how would I go about solving it?

- Math - Trig Substitution -
**Damon**, Monday, September 8, 2008 at 5:19am∫ x^3√(9-x^2) dx

So then I know that

x = 3sinθ

dx = 3cosθdθ

When I substitute, it becomes

∫ (3sinθ)^3 * √(9-(3sinθ)^2) * 3cosθdθ

BUT √(9-(3sinθ)^2) = 3 √ (1-sin^2)θ

1 - sin^2 = cos^2

= ∫ (27sin^3θ * (3 - 3 COS θ )* 3cosθdθ

**Answer this Question**

**Related Questions**

Calculus AP - hi again im really need help TextBook: James Stewart:Essential ...

Precalc/Trig - Sorry there are quite a few problems, but I just need to know if ...

Pre-Calculus - If θ represents an angle such that sin2θ = tanθ - ...

Trig - Prove (3cosθ-4sinθ)^2+(4cosθ+3sinθ)^2=25

Math - Find all solution of the trigonometric equation 3cosθ-√3=0 for...

Trig - Given that tan θ = - (√3/8) and θ is in QII, find the ...

trig - An object Is propelled upward at an angle θ, 45° < θ<90...

Integral Calculus - Solve using Integration by Substitution : ∫√x2-...

math trigono - 1. If tanθ = –√3 , what is the value of cot ? 2. ...

trigonometry help please :( - 2) Simplify √-1-4/5-√-1 A.-1/24+19/24i...